2002
DOI: 10.1142/s0218271802001950
|View full text |Cite
|
Sign up to set email alerts
|

Daily Variation in Cosmic Ray Intensity on Different Geomagnetic Conditions

Abstract: A new concept of data analysis has been attempted for studying the long/short term daily variations in cosmic ray (CR) intensity recorded with neutron monitors/meson telescopes. Fourier Technique has been applied on four different types of groups of days chosen according to their different geomagnetic conditions. The selected groups are 60 quietest days (60 QD), 120 quiet days (120 QD), continuous quiet days (CQD) and All Days (AD) in a year. CQD is a new set of days selected on the basis of Ap and Kp values. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, differences in the observed rate of approximately 1.7% and 2.4% between 0.33 -11 and 0.33 -Jan , respectively, were found during some times. In some situations, above one percent is considered to be a large change, particularly in studying certain cosmic ray variations such as the diurnal variations and Forbush decreases [25,26]. The above results evidently indicated that one should carefully choose the suitable pressure correction prior to any cosmic ray modulation studies [27].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, differences in the observed rate of approximately 1.7% and 2.4% between 0.33 -11 and 0.33 -Jan , respectively, were found during some times. In some situations, above one percent is considered to be a large change, particularly in studying certain cosmic ray variations such as the diurnal variations and Forbush decreases [25,26]. The above results evidently indicated that one should carefully choose the suitable pressure correction prior to any cosmic ray modulation studies [27].…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, some extraterrestrial factors affecting either the muon observations or the atmospheric pressure cannot be excluded [22]. It is obvious that the broad range of barometric coefficients supports the idea that the determination of over longer periods is of great importance for any cosmic ray detecting experiment and modulation study [16,21,[23][24][25]. Figure 3 demonstrates the diversity of using different values of to correct the effect of the atmospheric pressure on the muon rate.…”
Section: Resultsmentioning
confidence: 97%
“…This variability is a reflection of the continually changing conditions in the interplanetary space [2]. The systematic and significant deviations in the amplitude/phase of the diurnal/semi-diurnal anisotropy from the average values are known to occur in association with strong geomagnetic activity [3]. Rao et al [4] have shown that the enhanced diurnal variation of high amplitude events exhibits a maximum intensity in space around the anti-garden hose direction and a minimum intensity around the garden hose direction.…”
Section: Introductionmentioning
confidence: 99%
“…Search for an efficient scheme of population transfer is also one of the major goals of optimal control theory (OCT), a powerful and sometimes mathematically very sophisticated technique [16][17][18][19][20]. The OCT algorithm has been applied successfully to a broad variety of physical and chemical systems [21][22][23][24][25][26][27][28][29][30]. It intrinsically accounts for the quantummechanical interference between many pathways connecting initial and target state in a quantum system.…”
Section: Introductionmentioning
confidence: 99%